Masculinity, law, and the family - Collier, Richard, 1961- (Routledge, 1995)
Masculinity, Law and Family examines the construction of masculinity in a variety of areas of law pertaining to the family. Throughout, Richard Collier integrates recent theoretical developments in legal studies with a social theory of gender, the family and the social construction of masculinity. After an overview of theoretical positions and a critique of traditional legal theory, Richard Collier focusses on the legal regulation of homosexuality and transsexualism to show how confined the view of masculine sexuality is in legal discours. These arguments are further elaborated in a discussion of non-consummation, adultery and divorce, as well as fatherhood and paternity. Masculinity, Law and Family is of central importance to our understanding of the social and political dimension of masculinity.